Uropathogenic Escherichia coli Potentiates Type 1 Pilus-Induced Apoptosis by Suppressing NF-κB - Klumpp, David J. (American Society for Microbiology, 2001)
Urinary tract infections (UTIs) are among the most common inflammatory diseases. Acute UTIs are typically caused by type 1-piliated Escherichia coli and result in urothelial apoptosis, local cytokine release, and neutrophil infiltration. To examine the urothelial apoptotic response, a human urothelial cell line was incubated with various E. coli isolates and was then characterized by flow cytometry. Uropathogenic E. coli (UPEC) induced rapid urothelial apoptosis that was strictly dependent upon interactions mediated by type 1 pili. Interestingly, nonpathogenic HB101 E. coli expressing type 1 pili induced apoptosis at approximately 50% of the level induced by UPEC, suggesting that pathogenic strains contribute to apoptosis by pilus-independent mechanisms. Consistent with this possibility, UPEC blocked activity of an NF-κB-dependent reporter in response to inflammatory stimuli, yet this effect was independent of functional type 1 pili and was not mediated by laboratory strains of E. coli. UPEC suppressed NF-κB by stabilizing IκBα, and UPEC rapidly altered cellular signaling pathways. Finally, blocking NF-κB activity increased the level of piliated HB101-induced apoptosis to the level of apoptosis induced by UPEC. These results suggest that UPEC blocks NF-κB and thereby enhances type 1 pili-induced apoptosis as a component of the uropathogenic program.